IMPLEMENTASI MIKROKONTROLER NODEMCU ESP8266 SEBAGAI PENGENDALI PERANGKAT ELEKTRONIK BERBASIS VOICE ASSISTANT - Muhammad Qosdy Jauharul Arzaq; Irwan Alnarus Kautsar; Azmuri Wahyu Azinar (Politeknik Bisnis Indonesia, 2024)
One prominent development is the concept of the Internet of Things (IoT), which connects various physical devices via an internet network. By leveraging platforms like the NodeMCU ESP8266, IoT enables integration between the digital and physical worlds, opening up new opportunities in device monitoring and control. This research aims to implement the NodeMCU ESP8266 microcontroller as a voice assistant-based electronic device controller, by designing and implementing electronic device control using the basis of the Internet of Things (IoT) on a smartphone platform by utilizing the sistem development life cycle (SDLC) model. The research results show that the NodeMCU ESP8266 microcontroller is capable of controlling electronic devices based on voice assistants well. The sistem is able to detect and process voice commands with high accuracy, as well as control connected electronic devices efficiently, with an average success percentage of voice commands of 96.5%.